Validation process for electrical charge tomography system using digital imaging technique - Isa, Mohd Daud; Rahmat, Mohd Fua'ad; Jusoff, Kamaruzaman; Raja Hussin, Tengku Ahmad Badrul Shah (Canadian Center of Science and Education, 2009)
Electrical charge tomography (EChT) is a non-invasive imaging technique that is aimed to reconstruct the image of material being conveyed based on data measured by electrodynamics sensor installed around the pipe. The method to ensure the stability and accuracy of the image reconstruction should be applied to obtain a meaningful image reconstruction results. In this paper, Least square with regularization (LSR) method was introduced to reconstruct the cross-section image of material in gravity mode conveyor pipeline. Numerical analysis result based on data measured by sensor indicates that the algorithm is efficient to overcome the numerical instability. Instead of image reconstruction process, validation of the images is very important. It would be parts of verification process to the new image reconstruction method. In this system, digital imaging technique was used to interrogate the flow in pipeline around sensing area using CCD camera. It was found out that there is a good match between LSR method of image reconstruction and image capture by CCD camera due to the similarity of both images. This study implies that LSR method produced images that are stable and accurate as well as applicable for industrial use. It is suggested that another validation process should be conducted using duty ratio, signal to noise ration and structure correlation to validate the quality of image produced by LSR method.